Pendidikan Toleransi Beragama Berbasis Al-Qur’an dan Hadits: Suatu Kajian Literatur - Nuratika Nuratika; Abu Anwar; Sari Haryati (LPPM Institut Pendidikan Nusantara Global, 2026)
Religious tolerance education had been a fundamental issue in pluralistic societies, particularly in Indonesia, which is characterized by religious, cultural, and ethnic diversity. This article aimed to examine the concept of religious tolerance education based on the Qur’an and Hadith through a literature review approach. The study analyzed Qur’anic verses and the Hadith of the Prophet Muhammad that were relevant to the values of tolerance, moderation, and respect for differences in belief. The method employed was library research by analyzing primary sources in the form of the Qur’an and Hadith, as well as secondary sources consisting of relevant scholarly books and academic journal articles. The findings indicated that the Qur’an and Hadith explicitly and implicitly emphasized the principles of religious freedom, the prohibition of coercion in belief, justice, dialogue, and mutual respect among followers of different religions. Religious tolerance education grounded in these values was found to have the potential to strengthen religious moderation and to prevent extremist attitudes in social life. The study concluded that integrating the values of religious tolerance into Islamic education constituted a strategic necessity for building a harmonious and civilized society.